Effectiveness of Periodicity Theory in Enhancing Student’s Writing Skills - A. Alenezi, Ahmad; A. Alanezi, Manair; S. Alrashidi, Reem (International Journal of English Language Education, 2024)
This study investigates the integration of periodicity theory into teaching methodologies to address academic writing challenges among students. Periodicity theory focuses more on the cyclical nature of the writing process, offering insights into the organization and development of written discourse. This study examines the effectiveness of incorporating periodicity elements into teaching writing skills through a comprehensive methodology involving 10 students enrolled in the General English course. The results show significant improvements in students’ writing, with notable improvements in coherence, organization, and the incorporation of periodicity elements. However, not all students have similar learning speeds, leading to others in the study requiring further refinement in grammar and the inclusion of new Macro or Hyper-Themes. Despite the few students who did not improve significantly, the study showed a substantial increase in students’ writing skills when educators employ the periodicity concept.